Perbedaan Motorik Halus dan Motorik Kasar Balita Berdasarkan Status Stunting di Desa Passo - Goha, Maria Magdalena; Tiwery, Indah Benita; Tomasoa, Valensya Yeslin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
Stunting is a global public health issue that impacts fine and gross motor development in children. The prevalence of stunting remains high in Indonesia, particularly in areas like Passo Village, Ambon City. This study aims to analyze differences in fine and gross motor development among stunted and non-stunted children. A comparative study with a cross-sectional design was conducted on 40 toddlers (20 stunted, 20 non-stunted) selected via purposive sampling. Motor development was assessed using the Denver Developmental Screening Test II, and height was measured with a microtoise. Data were analyzed using the chi-square test at a significance level of p < 0.05. Among stunted children, 80% were classified as suspect in fine motor skills, compared to 20% in the non-stunted group (p = 0.000). For gross motor skills, 75% of stunted children were classified as suspect, compared to 25% in the non-stunted group (p = 0.000). Stunting significantly affects fine and gross motor development. Early interventions integrating nutritional programs and physical stimulation are essential to mitigate the long-term impact of stunting. Community-based programs focusing on nutrition, parental education, and physical stimulation are recommended to improve motor development in stunted children.